ANALISIS PEMILIHAN LOKASI RUMAH MAKAN PADANG MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Sambudi Hamali; Muhammad Daniel Habiburrahman (Jurnal Ekonomi Sakti, 2023)
As time goes by, business drivers continue to expand their businesses as innovations advance the level of the economy. One of the economic sectors that relies on expanding business branches is the culinary industry. There are several business actors in the culinary field in Indonesia, PT. XYZ is one of them. PT. XYZ is a company in Indonesia engaged in the archipelago's culinary specialities. This study aims to determine the exact location of the new branch of PT. XYZ uses the Analytical Hierarchy Process (AHP) method. The data collection method in this study is an interview and questionnaire from the director of PT. XYZ. This study's analytical decision-making method uses the Analytical Hierarchy Process with SuperDecision V2 software. The result of this research is that there is an advantage of the location of Bogor City as a new business location which was previously compared to other alternative locations Cisarua Puncak area.